ANALISIS DEFISIT KEMBAR DAN FELDSTEIN-HORIOKA PUZZLE DI INDONESIA - Rastri Paramita; Mutiara Shinta Andini (Pusat Kajian Anggaran, 2019)
This study aims to empirically examine the twin deficit and Feldstein-Horioka puzzle in the case of Indonesia period 1972-2017 and main factor that affect current account deficit in Indonesia for the last ten years. Granger’s causality is used to know the influence of budget deficit against current account balance. The Autoregressive Distributed Lag-Error-Correction Model (ARDL-ECM) approaches are applied to estimate the long run and short run relationships. The estimation results that the budget deficit is not have impact on the current account deficit in Indonesia. Meanwhile, does not occur long run cointegration based on THE ARDL. ECM results that budget deficit and investment have a short term influence the current account deficit. Based on the ARDL-ECM results, it can be concluded that the theory of Feldstein-Horioka Puzzle in the period 1972-2017 proved to occur in Indonesia. The main factor that influences the current account balance in Indonesia generally is the increase in primary income payments due to financial transactions that are always surplus and will appear forwards as payments. The condition of the current account is sustainable in a weak form means financed by financial transactions needs to be wary of negative risks in the future. The Foreign Direct Investment (FDI), Other Investments, and particularly the Portfolio Investments to prevent the occurrence of the risk of abrupt reversals which is crisis prone. So that the focus of the direction of government policy should be able to carry out stimulus to increase domestic direct investment, especially those are export oriented or substitute for domestic import needs and deepening the domestic financial market in portfolio sub-investments also other investments.